2011
DOI: 10.1590/s0104-11692011000300024
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and sexuality: integrative review of papers published by the Latin-American Journal of Nursing and Brazilian Journal of Nursing

Abstract: This study departs from the assumption that studies addressing sexuality in the field of nursing present changes and broaden the scope of discussion to include gender and sexual rights, although a strong tendency to link sexuality to its biological aspects is still observed.This study identifies the state-of-the-art of studies addressing sexuality published by two international journals: Latin American Journal of Nursing and The Brazilian Journal of Nursing. The sources were papers published in both periodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
3
0
7
Order By: Relevance
“…15 Health professionals are key actors involved in the information sharing process about AIDS, prevention, treatment, recovery and, above all, should be seen as partial protagonists of changes in the epidemiological profile. 16 The school was the fourth most cited source for both types of condoms. In this context, a search aimed at university students in the health area identified that most of the information on the prevention of STIs and HIV was also acquired during school period.…”
Section: Health Campaigns Broadcast On Television and The Very Open Cmentioning
confidence: 99%
“…15 Health professionals are key actors involved in the information sharing process about AIDS, prevention, treatment, recovery and, above all, should be seen as partial protagonists of changes in the epidemiological profile. 16 The school was the fourth most cited source for both types of condoms. In this context, a search aimed at university students in the health area identified that most of the information on the prevention of STIs and HIV was also acquired during school period.…”
Section: Health Campaigns Broadcast On Television and The Very Open Cmentioning
confidence: 99%
“…Apreendeu-se que a sexualidade não era plenamente compreendida pelos participantes como fator individual e constituinte da personalidade humana, que se integram de forma indissociável aos demais aspectos da vida e relaciona-se aos aspectos biopsicossociais e espirituais do indivíduo, não se restringindo às questões da corporeidade, ao ato sexual, nem tão somente às características sexuais (3) . Por isso, o percurso dialógico da pesquisa percorreu estratégias dialógicas distintas até que os atores pudessem desvelá-la como a forma de cada indivíduo se expressar, se posicionar, se relacionar, tanto na vida amorosa e sexual como social (3,12) .…”
Section: Discussionunclassified
“…Por isso, o percurso dialógico da pesquisa percorreu estratégias dialógicas distintas até que os atores pudessem desvelá-la como a forma de cada indivíduo se expressar, se posicionar, se relacionar, tanto na vida amorosa e sexual como social (3,12) . Nesse sentido, puderam de fato dialogar sobre as dimensões biológicas, psicológica e social da sexualidade apropriando-se dessa nova perspectiva ampla até então pouco conhecida e valorizada.…”
Section: Discussionunclassified
See 2 more Smart Citations